Physical Characteristics of Chitosan Based Film Modified With Silica and Polyethylene Glycol - F. Widhi Mahatmanti; Nuryono Nuryono; Narsito Narsito (Universitas Gadjah Mada, 2014)
Recently, development of film materials is focused on finding the films with high chemical and physical stabilities. Organic based material such as chitosan produces films with low physical stability, and hence addition of inorganic materials necessary. In this research, the effect of silica and polyethylene glycol (PEG) addition on the properties of chitosan based films has been investigated. Precursors used to produce films included chitosan with the deacetylation degree of 83% and sodium silicate solution as the silica source. A simple synthesis in a one-pot process was carried out by mixing 1%(w) of chitosan solution in 2%(v/v) acetate acid and sodium silicate solution (27% SiO2) in various composition ratios and casting the solution on a glass dish. The tensile strength and percentage of elongation decrease with increasing the silica content. The tensile strength tends to decline with addition of PEG, but the elongation percentage of the film increases. Hydrophilicity of the film decreases with the addition of silica and increases with the addition of PEG. The addition of silica and PEG does not change significantly the morphology of the film and functional groups indicating the domination of physical interaction among active sites in the film components.